Hydrographic changes in the tropical and extratropical Pacific during the last deglaciation. (18th September 2013) - Rodríguez‐Sanz, Laura; Mortyn, P. Graham; Herguera, Juan C.; Zahn, Rainer
<x xml:space="preserve">Abstract</x> [1] Fine‐scale, paired Mg/Ca‐δ18O profiles (Globigerinoides ruber white, sensu lato) from the San Lázaro Basin (SLB) at 25°N in the Northeast Pacific reveal a transition from a predominant presence of tropical/subtropical waters during the last glacial termination (T1) to an increasing influence of fresh and cold California Current waters toward the Holocene. Changing atmospheric circulation patterns over the Northeast Pacific in step with the demise of the Northern Hemisphere ice sheets and/or with a shift from El Niño‐ to La Niña‐like conditions toward the Holocene are prime candidates to explain this water mass change. δ18OSW‐IVC increases of 0.5–0.7‰ during the Younger Dryas (YD) and Heinrich stadial 1 (HS1) at the SLB are observed in a number of δ18OSW‐IVC records from the tropical Pacific, more directly influenced by changes in the position of the Intertropical Convergence Zone (ITCZ). Conditioning by ITCZ migration of the tropical Pacific Ocean towards salinity increase during YD and HS1, and the subsequent advection of those water masses as far north as 25°N likely accounted for the reconstructed hydrographical changes at the SLB. A larger influence of tropical water masses as far north as 25°N plausibly contributed to changes in the atmospheric moisture transports to western North America and affected the regional hydrological cycle across T1. Finally, the fine‐scale resolution of our δ18OSW‐IVC record allows pinpointing a shift from relative salty to fresh surface conditions at 16.2 ka, signaling that the two‐phase structure of HS1 is plausibly a ubiquitous feature of the northern tropical to extratropical ocean‐atmosphere dynamics.